Feline Aortic Thromboembolism Diagnosed by Thermography - da Silva, Diego Matos; Caramalac, Silvana Marques; Caramalac, Simone Marques; Gimelli, Amanda; Palumbo, Mariana Isa Poci (Acta Scientiae Veterinariae, 2022)
Background: In cats, arterial thromboembolism is one of the most devastating diseases, with an acute presentation, and is often caused by undiagnosed cardiomyopathy. Defined as the obstruction of one or more arterial lumens by emboli, the arterial thromboembolism is responsible for hypoperfusion signs. As the temperature of the skin surface is directly related to tissue perfusion,thermography can be promising for the early diagnosis of thromboembolism. Therefore, this study reports the importance of thermography as a complementary examination for the diagnosis of thromboembolism in the abdominal aorta of a domestic cat. Case: A 4-year-old mixed-breed cat weighing 2.95 kg was presented with a history of sudden onset paraplegia, apathy, and pain when handled, with greater intensity in the sacro-coccidian region. During physical exam, it was noted that the femoral artery pulse was undetectable bilaterally during manual pulse measurement. Superficial and deep sensitivity in the pelvic limbs and proprioception were also absent and the plantar cushions and nail beds of the posterior limbs were pale to cyanotic. Thermographic images revealed that the temperature of both hind limbs was lower than that of forelimbs, with difference of 3.2ºC and 2.9ºC between the left and right limbs, respectively. Doppler ultrasonography revealed the absence of pulse and flow in the femoral arteries bilaterally. Electrocardiography revealed sinus tachycardia, with a heart rate of 250 bpm. Echocardiography revealed dilation of the left atrium and concentric cardiac hypertrophy. After 24 h, due to the worsening of the clinical condition and unfavorable prognosis, the animal was euthanized and sent for necropsy. Necropsy revealed that the arterial lumen of the caudal abdominal aorta and bifurcation of the iliac arteries were obliterated, with a 0.6 cm saddle thrombus adhered to the arterial wall. In addition, left ventricular thickening indicative pf hypertrophic cardiomyopathy was observed. In the left atrium, a thrombus was observed that filled the entire chamber. Discussion: Thermography is a fast and non-invasive method, and therefore, it is a tool of great relevance in emergencies. Previous study showed that a minimum temperature difference of 2.4°C between the affected and unaffected limbs has excellent specificity and high sensitivity for the diagnosis of feline aortic thromboembolism. In this report, the temperature differences between the affected and unaffected limbs on the left and right sides were found to be 3.2°C and 2.9°C, respectively, corroborated this finding. Cats with cardiomyopathies are predisposed to the development of thrombi, and rarely manifest heart disease. Here, the cat was diagnosed with hypertrophic cardiomyopathy during the diagnostic investigation for arterial thromboembolism, which is consistent with the usual findings because feline hypertrophic cardiomyopathy progresses silently with few clinical manifestations in the early stages. Clinical diagnosis of arterial thromboembolism can be made based on the presence of some physical examination findings, such as pain and paralysis of the affected limbs, absence of a femoral pulse, cold extremities, and pale or cyanotic cushions. In this report, thermography proved to be an accurate, quick, and non-invasive method for the assessment of vascular alterations that affected the pelvic limbs of the cat. Complementary examinations confirmed the presence of hypertrophic cardiomyopathy and necropsy revealed the presence of thrombus. Keywords: cyanosis, hypertrophic cardiomyopathy, ischemia, temperature.